The role of autonomous ESP learning in acquiring transversal professional development skills in Higher Education - Athanasiou, Androulla; Kakoulli-Constantinou, Elis; Burston, Jack (My University, 2024)
The rapid developments in a globalised 21st Century world have brought about changes and increased competitiveness in the employability of graduates. Acknowledging these developments and the need for innovation, the European Union recognises the need for education and training beyond the classroom (UNESCO, 2020). Hence, Higher Education (HE) is crucial in developing transversal skills and preparing undergraduates for the labour market. Essential therefore is developing independent learning habits and a collaborative lifelong learning mindset. Likewise, competence in English at a B1 CEFR (Common European Framework of References for Languages) level is a prerequisite of independent learning in any field. Lastly, autonomous learning also depends on knowing how to exploit ubiquitous digital technologies to extend language learning into daily life. This paper aims to provide suggestions to practitioners about how the teaching of English for Specific Purposes (ESP) courses need to be approached as a critical autonomous learning skill for professional knowledge acquisition, task accomplishment and interpersonal communication. It advocates for a blended teaching and learning mode, tailored to future graduates’ needs. Cloud technologies, such as Google Workspace for Education (Google, 2023), potentially offer an effective type of support for the development of transversal competencies in the context of ESP in HE.
Keywords: Applied Linguistics; Language Education; Technology in Education